Melatonin protects vertebral endplate chondrocytes against apoptosis and calcification via the Sirt1‐autophagy pathway. Issue 1 (24th October 2018) - Zhang, Zengjie; Lin, Jialiang; Tian, Naifeng; Wu, Yaosen; Zhou, Yifei; Wang, Chenggui; Wang, Qingqing; Jin, Haiming; Chen, Tingting; Nisar, Majid; Zheng, Gang; Xu, Tianzhen; et al.
Abstract: Melatonin is reportedly associated with intervertebral disc degeneration (IDD). Endplate cartilage is vitally important to intervertebral discs in physiological and pathological conditions. However, the effects and mechanism of melatonin on endplate chondrocytes (EPCs) are still unclear. Herein, we studied the effects of melatonin on EPC apoptosis and calcification and elucidated the underlying mechanism. Our study revealed that melatonin treatment decreases the incidence of apoptosis and inhibits EPC calcification in a dose‐dependent manner. We also found that melatonin upregulates Sirt1 expression and activity and promotes autophagy in EPCs. Autophagy inhibition by 3‐methyladenine reversed the protective effect of melatonin on apoptosis and calcification, while the Sirt1 inhibitor EX‐527 suppressed melatonin‐induced autophagy and the protective effects of melatonin against apoptosis and calcification, indicating that the beneficial effects of melatonin in EPCs are mediated through the Sirt1‐autophagy pathway. Furthermore, melatonin may ameliorate IDD in vivo in rats. Collectively, this study revealed that melatonin reduces EPC apoptosis and calcification and that the underlying mechanism may be related to Sirt1‐autophagy pathway regulation, which may help us better understand the association between melatonin and IDD.